Symbolic Interaction of Communication on Social Drug Users’ Community in Jakarta - Edison Hutapea; Yuli Marlina; Fery Sanjaya (LPPM Universitas Bina Sarana Informatika, 2022)
This article considers how communication is very capable and changeable in nation’s culture. Breathtakingly, this phenomenon was afflicted in metropolitan community in Jakarta as a result of globalization which is spread to all civilizations of nations in the world. The differences in perception of each individual equally obtain stimulate can occur in their interaction, the freedom of individual is to interpret the existing situation makes this research is needed due to the subject is interaction’s people based on perspective of symbolic interaction. The result have shown the drug users in Jakarta created a new communication symbols to disguise the terms of drugs in their social environment into the domain of the community. Moreover, youth groups with a very complex social life and inquisitive who wants to try a new thing and imitate easily in part of the foreign culture such as drugs is grow up rapidly. The research used symbolic interaction analysis and the researcher revealed the symbols and the meanings of communication based on the theory of symbolic interactionism; objectivity, and internalization where user makes specialties in their interactions between drug users in Jakarta